2012
DOI: 10.3747/pdi.2011.00308
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Patients, Families, and Health Care Professionals on Decision-Making about Dialysis Modality—the Good, the Bad, and the Misunderstandings!

Abstract: ♦ Objectives: This study explored the factors influencing decision-making about dialysis modality, integrating the perspectives of patients, their families, and health care professionals within an Asian population. The study further sought to understand the low penetration rate of peritoneal dialysis (PD) in Singapore. ♦ Methods: A sample of 59 participants comprising pre-dialysis patients, dialysis patients, caregivers, and health care professionals (HCPs) participated in semistructured interviews to explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 47 publications
2
38
3
1
Order By: Relevance
“…In contrast to other studies, 3,8 the YoDDA evaluation found the views of family and professionals were important in treatment decision-making, but not the views of other patients. Forty-five percent of referred patients in the intervention group were given the YoDDA booklet with a by-center variation of 14%-49%.…”
contrasting
confidence: 88%
“…In contrast to other studies, 3,8 the YoDDA evaluation found the views of family and professionals were important in treatment decision-making, but not the views of other patients. Forty-five percent of referred patients in the intervention group were given the YoDDA booklet with a by-center variation of 14%-49%.…”
contrasting
confidence: 88%
“…30 In contrast, other studies have noted that depression and anxiety in patients on PD are equal or even higher than those reported for patients on HD. 25,31 By virtue of PD being a home-based dialysis technique, individuals may feel sustained distress over the daily responsibility of their own health and well-being or medicalization of home environment that may act as constant reminder of their ill health.…”
mentioning
confidence: 39%
“…However, they do not usually receive the available information needed [18]. Thus, pre-dialysis programmes need to be designed for caregivers in order to help them make informed decisions about the dialysis method their patient will follow [1].…”
Section: Support Information Of Caregiversmentioning
confidence: 99%
“…A large proportion of family members take full responsibility for making decisions about the dialysis method the patients will follow, taking into consideration the opportunity to maintain their lifestyle and the possible risk of the therapy. They also take into account their priorities and their capability to manage home haemodialysis [1]. However, sometimes family caregivers have to take diicult decisions, such as interruption of dialysis therapy or referring their patients to hospice services [18].…”
Section: Caregivers' Role In Haemodialysis Patientsmentioning
confidence: 99%
See 1 more Smart Citation